1977
DOI: 10.1099/0022-1317-36-1-93
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of a Virus from Tellina tenuis to Infectious Pancreatic Necrosis Virus

Abstract: SUMMARYThe physicochernical and serological properties of a virus isolated from the bivalve mollusc, Tellina tenuis, have been examined. The virus has a diam. of 59 nrn, sediments at 43oS in sucrose gradients and bands at a density of I-32 g/ml in CsC1. The virus contains RNA with a tool. wt. about 2.8 × IO 6 as estimated by polyacrylamide gel electrophoresis but in sucrose gradients the RNA sediments at I4S. The virus RNA is resistant to ribonuclease under conditions in which ribosomal RNA and the single stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 1 publication
6
48
1
Order By: Relevance
“…For routine purposes, however, we recommend that the ELISA technique is used to replace the confirmatory virus neutralization test when at least minimal c.p.e, is observed. The technique was specific for IPNV serogroup 1 as it was demonstrated that only IPNV serotypes Sp, Ab and Vr crossreacted, whereas 10 other viruses pathogenic for rainbow trout or other fish species did not; TV-1 (IPNV serogroup 2) was one of the viruses that did not cross-react with IPNV serotype Sp antiserum, in agreement with the neutralization data of Underwood et al (1977) but at variance with those of Macdonald & Gower (1981). It was possible to rapidly serotype IPNV using coating ~-globulin and conjugates prepared from antiserum against each of the three serogroup 1 serotypes, and there was a good correlation between our virus-neutralization data and ELISA results except with serotype Vr antiserum.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…For routine purposes, however, we recommend that the ELISA technique is used to replace the confirmatory virus neutralization test when at least minimal c.p.e, is observed. The technique was specific for IPNV serogroup 1 as it was demonstrated that only IPNV serotypes Sp, Ab and Vr crossreacted, whereas 10 other viruses pathogenic for rainbow trout or other fish species did not; TV-1 (IPNV serogroup 2) was one of the viruses that did not cross-react with IPNV serotype Sp antiserum, in agreement with the neutralization data of Underwood et al (1977) but at variance with those of Macdonald & Gower (1981). It was possible to rapidly serotype IPNV using coating ~-globulin and conjugates prepared from antiserum against each of the three serogroup 1 serotypes, and there was a good correlation between our virus-neutralization data and ELISA results except with serotype Vr antiserum.…”
Section: Discussionsupporting
confidence: 74%
“…There was a low-level cross-reaction with IPN serotypes Ab and Vr reflecting virus neutralization data (Underwood et al, 1977), but no cross-reactions with any of the other viruses.…”
Section: Cross-reactions With Other Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the wide spread monitoring for aquatic birnaviruses in the freshwater and marine environments, only recently the IPNV American serotype (WB) has been isolat ed from turbot in Europe (Novoa et al, 1993b). Furthermore birnaviruses have been isolated from marine bivalves (Underwood et al, 1977;Lo et al, 1988;Rivas et al, 1993) and even from several species used as food for cultured fish. This is the case of rotifer (Brachionus plicatilis), other cultured marine fish larvae, and the fish species used as fresh food for turbot such as raw sand-eel (Ammodytes sp) and blue whiting (Micromesistius potassou) (Rivas et al, 1993).…”
Section: Viral Rna Electrophoresismentioning
confidence: 99%
“…Many viruses have been isolated from marine bi valve molluscs and shown to be pathogenic to hosts (Dobos et al, 1979;Elston and Wilkinson, 1985;Farley et al, 1972;Meyers, 1979;Oprandy et al, 1981;Underwood et al, 1977). In Taiwan, several viruses have been isolated from cultured hard clams, including CV-HB-1, CV-TS-1, CV-TS-8 of the family Birnaviridae (Lo et al, 1988) and HCV of family Reoviridae (Hsu et al, personal communication).…”
mentioning
confidence: 99%